No, because AB and BA are generally not equal. Matrix multiplication is not commutative.
So (A+B)^2 = A^2 + AB + BA + B^2 is the correct formula.
2007-01-25 20:06:49
·
answer #1
·
answered by John D 3
·
0⤊
0⤋
no,not in general,there is a condition:
if AB = BA => (A+B)^2 = (A+B)(A+B) = A^2 + AB + BA +B^2 =
A^2 + AB + AB + B^2 = A^2 + 2AB + B^2 = (A + B)^2
and:
if (A+B)^2 =A^2 + 2AB + B^2 =>
A^2 + AB + BA + B^2 = A^2 + 2AB + B^2 =>
AB + BA = 2AB => BA = AB
2007-01-26 04:02:05
·
answer #2
·
answered by farbod f 2
·
0⤊
0⤋
If A and B are n by n matrices
then (A+B)^2 = (A+B)(A+B)
= A.A + A.B + B.A + B.B
= A^2+ A.B + B.A + B^2
and only if A.B = B.A then (A+B)^2=A^2+2AB+B^2 which is not always the case in generally.
so first one need to find whether A.B = B.A for above expression to be true.
If A=B then one can easily say above staement to be true.
also if both A and B are diagonal matrix then above statemnt holds....
2007-01-26 04:15:33
·
answer #3
·
answered by rajeev_iit2 3
·
0⤊
0⤋
No,
The correct answer would be A^2 + AB +BA + B^2
This is because matrices are not commutative that is
AB does not equal BA, Therefore you can not add them.
2007-01-26 03:53:48
·
answer #4
·
answered by Mark T 1
·
3⤊
0⤋
No, because in matrices AB is not equal to BA .
hence (A+B)^2 = (A+B)(A+B) = A.A + A.B + B.A + B.B
= A^2+ A.B + B.A + B^2
2007-01-26 04:00:54
·
answer #5
·
answered by Anurag 2
·
0⤊
0⤋
No. The square root of A+B would have to be a tangent to the cosine of 2AB.
2007-01-26 03:50:52
·
answer #6
·
answered by Anonymous
·
0⤊
2⤋
Another two counter-examples are these one:
A (or B) = the nule matrix or the identity matrix
Ana
2007-01-27 01:00:44
·
answer #7
·
answered by MathTutor 6
·
0⤊
0⤋
In general, no. However, in the case where A and B are permutable it is true.
Doug
2007-01-26 04:21:34
·
answer #8
·
answered by doug_donaghue 7
·
0⤊
0⤋